Short Implant to Support Maxillary Restorations: Bone Stress Analysis Using Regular and Switching Platform - de Carvalho, Nivaldo Antonio; de Almeida, Erika Oliveira [UNESP]; Rocha, Eduardo Passos [UNESP]; Freitas, Amilcar Chagas; Anchieta, Rodolfo Bruniera; Kina, Sidney (Lippincott Williams & Wilkins, 2012)
Purpose: The aim of this study was to evaluate stress distribution on peri-implant bone simulating the influence of implants with different lengths on regular and switching platforms in the anterior maxilla by means of three-dimensional finite element analysis.Materials and Methods: Four mathematical models of a central incisor supported by an external hexagon implant (diameter, 5.0 mm) were created, varying the length (15.0 mm for long implants [L] and 7.0 mm for short implants [S]) and the diameter of the abutment platform (5.0 mm for regular models [R] and 4.1 mm for switching models [S]). The models were created using the Mimics 11.11 (Materialise) and SolidWorks 2010 (Inovart) software. Numerical analysis was performed using ANSYS Workbench 10.0 (Swanson Analysis System). Oblique forces (100 N) were applied to the palatine surface of the central incisor. The bone/implant interface was considered perfectly integrated. Maximum (sigma(max)) and minimum (sigma(min)) principal stress values were obtained.Results: For the cortical bone, the highest stress values (sigma(max)) were observed in the SR (73.7 MPa) followed by LR (65.1 MPa), SS (63.6 MPa), and LS (54.2 MPa). For the trabecular bone, the highest stress values (sigma(max)) were observed in the SS (8.87 MPa) followed by the SR (8.32 MPa), LR (7.49 MPa), and LS (7.08 MPa).Conclusions: The influence of switching platform was more evident for the cortical bone in comparison with the trabecular bone for the short and long implants. The long implants showed lower stress values in comparison to the short implants, mainly when the switching platform was used.
Keywords: Bone biology; implantology; osseointegration; prosthodontics